Investigating the Antioxidant, Antimicrobial and Sensory Effects of Honey Propolis Extract as a Natural Preservative in Beef Burgers - Forough Fakhraei; Alireza Masoud Nia; Fatemeh Zia Ziabari; Hamed Kioumarsi (Bioactivities, 2025)
In this study, the antioxidant, antimicrobial and sensory effects of honey propolis extract as a natural preservative in beef burgers were investigated. First, propolis extract was produced at different percentages (0.5, 1.0, and 2.0%), and the control treatment, containing 0% propolis extract, was produced with a beef burger. The pH, antioxidant 2,2-diphenyl-1-picrylhydrazyl (DPPH), thiobarbituric acid (TBA), total volatile base nitrogen (TVB-N), and microbial characteristics (total microbial count, Escherichia coli, Staphylococcus aureus, mold, and yeast) and sensory characteristics (color, smell, texture and overall acceptance) during the storage period were subsequently investigated over a period of 8 days (0, 4, and 8). The results of the evaluation of different properties revealed that adding propolis extract to hamburger samples caused a significant decrease in pH, TBA, TVN, and microbial properties (total microbial count, E. coli, S. aureus, mold, and yeast) (p < 0.05). On the other hand, the amount of antioxidant property and sensory evaluation (color, smell, texture, and overall acceptance) also increased with the addition of propolis extract (p < 0.05). Additionally, the duration of storage caused a significant increase in pH, TBA, TVN, and microbial characteristics (total microbial count, E. coli, S. aureus, and mold and yeast), and a reduction in antioxidant properties and sensory evaluation (color, smell, texture, and overall acceptability) were found in hamburger samples (p < 0.05). The use of 2% propolis extract improved the oxidation properties and maintained the sensory properties during 8 days of storage for hamburger. Therefore, the use of 2% propolis extract improves the antioxidant and antimicrobial properties of hamburgers during storage and is a superior treatment.